Integrated Genome-Wide Analysis of MicroRNA Expression Quantitative Trait Loci in Pig Longissimus Dorsi Muscle - Daza, Kaitlyn R.; Velez-Irizarry, Deborah; Casiró, Sebastian; Steibel, Juan P.; Raney, Nancy E.; Bates, Ronald O.; Ernst, Catherine W. (Frontiers in Genetics, 2021)
Determining mechanisms regulating complex traits in pigs is essential to improve the production efficiency of this globally important protein source. MicroRNAs (miRNAs) are a class of noncoding RNAs known to post-transcriptionally regulate gene expression affecting numerous phenotypes, including those important to the pig industry. To facilitate a more comprehensive understanding of the regulatory mechanisms controlling growth, carcass composition, and meat quality phenotypes in pigs, we integrated miRNA and gene expression data from longissimus dorsi muscle samples with genotypic and phenotypic data from the same animals. We identified 23 miRNA expression Quantitative Trait Loci (miR-eQTL) at the genome-wide level and examined their potential effects on these important production phenotypes through miRNA target prediction, correlation, and co-localization analyses. One miR-eQTL miRNA, miR-874, has target genes that co-localize with phenotypic QTL for 12 production traits across the genome including backfat thickness, dressing percentage, muscle pH at 24h post-mortem, and cook yield. The results of our study reveal genomic regions underlying variation in miRNA expression and identify miRNAs and genes for future validation of their regulatory effects on traits of economic importance to the global pig industry.